SN 2017ivv: two years of evolution of a transitional Type II supernova. Issue 1 (23rd September 2020) - Gutiérrez, C P; Pastorello, A; Jerkstrand, A; Galbany, L; Sullivan, M; Anderson, J P; Taubenberger, S; Kuncarayakti, H; González-Gaitán, S; Wiseman, P; Inserra, C; Fraser, M; et al.
ABSTRACT: We present the photometric and spectroscopic evolution of the Type II supernova (SN II) SN 2017ivv (also known as ASASSN-17qp). Located in an extremely faint galaxy ( Mr  = −10.3 mag), SN 2017ivv shows an unprecedented evolution during the 2 yr of observations. At early times, the light curve shows a fast rise (∼6−8 d) to a peak of ${\it M}^{\rm max}_{g}= -17.84$ mag, followed by a very rapid decline of 7.94 ± 0.48 mag per 100 d in the V band. The extensive photometric coverage at late phases shows that the radioactive tail has two slopes, one steeper than that expected from the decay of 56 Co (between 100 and 350 d), and another slower (after 450 d), probably produced by an additional energy source. From the bolometric light curve, we estimated that the amount of ejected 56 Ni is ∼0.059 ± 0.003 M⊙. The nebular spectra of SN 2017ivv show a remarkable transformation that allows the evolution to be split into three phases: (1) Hα strong phase (<200 d); (2) Hα weak phase (between 200 and 350 d); and (3) Hα broad phase (>500 d). We find that the nebular analysis favours a binary progenitor and an asymmetric explosion. Finally, comparing the nebular spectra of SN 2017ivv to models suggests a progenitor with a zero-age main-sequence mass of 15–17 M⊙ .